2021
DOI: 10.1371/journal.pone.0252272
|View full text |Cite
|
Sign up to set email alerts
|

Apple cider vinegar soaks do not alter the skin bacterial microbiome in atopic dermatitis

Abstract: Introduction Atopic dermatitis is a common skin disease characterized by altered cutaneous immunity in which patients often exhibit lower skin microbiota diversity compared to healthy skin and are prone to colonization by Staphylococcus aureus. Apple cider vinegar has been shown to have antibacterial effects; however, its effects on the skin microbiome have not previously been well-described. Objectives We aimed to examine the effects of topical dilute apple cider vinegar soaks on Staphylococcus aureus abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However, a study examined the effects on Staphylococcus aureus abundance after 14 days of topical dilute apple cider vinegar (0.5% acetic acid) in 11 subjects with AD compared with 11 healthy controls. The results suggested no difference in the mean abundance of S. aureus in AD subjects and no significant differences in the skin bacterial microbiome of healthy control subjects [ 88 ]. Another recent study showed that diluted apple cider vinegar did not affect skin barrier integrity but caused skin irritation in most subjects [ 89 ].…”
Section: The Use Of Additivesmentioning
confidence: 99%
“…However, a study examined the effects on Staphylococcus aureus abundance after 14 days of topical dilute apple cider vinegar (0.5% acetic acid) in 11 subjects with AD compared with 11 healthy controls. The results suggested no difference in the mean abundance of S. aureus in AD subjects and no significant differences in the skin bacterial microbiome of healthy control subjects [ 88 ]. Another recent study showed that diluted apple cider vinegar did not affect skin barrier integrity but caused skin irritation in most subjects [ 89 ].…”
Section: The Use Of Additivesmentioning
confidence: 99%
“…Local application of SCFAs can promote the growth of beneficial microbes, and topical administration of probiotics promotes the release of SCFAs to mitigate skin inflammation ( Kim C. H. et al, 2015 ). In a trial to validate acetate for AD, topical application of apple cider vinegar (0.5% acetate) for 2 weeks did not affect the skin microbiome of healthy subjects and AD patients compared to the water placebo group, and also did not prevent the colonization of S. aureus on the inflamed skin ( Luu et al, 2021 ). However, no significant difference was observed in the diversity of the skin microbiome between the AD patients and healthy subjects at baseline ( Luu et al, 2021 ).…”
Section: Scfa-based Therapy For Inflammatory Skin Diseasesmentioning
confidence: 99%
“…In a trial to validate acetate for AD, topical application of apple cider vinegar (0.5% acetate) for 2 weeks did not affect the skin microbiome of healthy subjects and AD patients compared to the water placebo group, and also did not prevent the colonization of S. aureus on the inflamed skin ( Luu et al, 2021 ). However, no significant difference was observed in the diversity of the skin microbiome between the AD patients and healthy subjects at baseline ( Luu et al, 2021 ). Therefore, the inhibitory effect of apple cider vinegar on S. aureus growth may depend on the bacterial strain and the levels of acetate ( Fraise et al, 2013 ).…”
Section: Scfa-based Therapy For Inflammatory Skin Diseasesmentioning
confidence: 99%
“…216 We found in the review that daily soaks in 0.5% apple cider vinegar do not work on altering the bacterial microbes of the skin in AD. 217 Dilute apple cider vinegar soaks have no significant effect on skin barrier integrity; however, they do not cause skin irritation in most subjects. 218 The existing data cannot support this argument.…”
Section: Natural Products For the Treatment Of Admentioning
confidence: 99%